Implementation of blended learning in Indonesian Language subject at Senior High School 05 Bombana - Ana, Haerun; Udu, Sumiman; Saidiman, Saidiman (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This study aims to analyze the planning, implementation, and evaluation of the blended learning model at SMA Negeri 05 Bombana during the Covid-19 pandemic. The approach used in this research is qualitative with descriptive analysis to obtain a comprehensive picture of the implementation of blended learning. The research variables include blended learning-based learning policy, human resource readiness, learning application management, learning planning, teacher role, student readiness, learning strategies and methods, learning media, application, learning system, and learning process and outcomes. The results show that the planning of blended learning has run well with appropriate policies, technical guidance for teachers, and operator readiness. The implementation was effective, marked by the active role of teachers, the enthusiasm of students, and the use of Google Classroom and WhatsApp applications. The evaluation showed that online and offline methods were well integrated, and students improved in cognitive and psychomotor aspects. Teachers use essay and multiple choice tests as learning evaluation. Teacher performance in learning was also high, with APKG II score of 91.6% (category A). This research shows that blended learning can be an effective solution in supporting the learning process during the pandemic.